2012
DOI: 10.1074/jbc.m111.266940
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Hypertrophy Is Positively Regulated by MicroRNA miR-23a

Abstract: Background:The molecular targets of miRNAs in the cardiac hypertrophic cascades remain to be fully identified. Results: Foxo3a is a target of miR-23a. Conclusion: miR-23a can mediate the hypertrophic signal through regulating Foxo3a. Significance: miR-23a and Foxo3a can be targets for the development of hypertrophic treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(65 citation statements)
references
References 52 publications
1
63
0
Order By: Relevance
“…The target mRNAs of miRNAs are being uncovered, including the verified targets for miR-10a, such as fms-related tyrosine kinase 1,27) cell adhesion molecule L1-like, 28) phosphatase and tensin homolog, 29) and EPH receptor A8 30) in some diseases. More importantly, miR-10a is found to repress TBX5 protein levels by targeting TBX5 3'UTR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The target mRNAs of miRNAs are being uncovered, including the verified targets for miR-10a, such as fms-related tyrosine kinase 1,27) cell adhesion molecule L1-like, 28) phosphatase and tensin homolog, 29) and EPH receptor A8 30) in some diseases. More importantly, miR-10a is found to repress TBX5 protein levels by targeting TBX5 3'UTR.…”
Section: Discussionmentioning
confidence: 99%
“…1,2) Although tremendous efforts have been made during the past decade, the underlying molecular mechanisms of cardiac hypertrophy are still poorly understood. 3,4) Thus, it is of great significance to identify key factors that may regulate cardiac hypertrophy.…”
mentioning
confidence: 99%
“…Cardiomyocytes were isolated from male mice (1-2 days) as we described 38 . Briefly, after dissection hearts were washed and minced in HEPES-buffered saline solution.…”
Section: Methodsmentioning
confidence: 99%
“…miR-23a is involved in cardiac hypertrophy as a downstream target of the calcineurin/NFAT pathway and targets the anti-hypertrophic protein, muscle ringfinger protein 1 (MURF1) [53]. Therapeutic studies in rodents using antagomir to silence miR-23a showed attenuation of cardiac hypertrophic growth in different models of HF [53,54] with the underlying mechanism involving direct targeting of the forkhead box O3 gene (FOXO3A), a transcription factor involved in the regulation of cardiac hypertrophy [54]. Moreover, miR-23a, similar to miR-199b, is regulated by the calcineurin/NFAT signaling pathway and it will be interesting to know how both microRNAs integrate to mediate calcineurin/NFAT signaling during cardiac hypertrophy and HF.…”
Section: Angiogenesismentioning
confidence: 98%